Biodegradation of Deoxynivalenol by Nocardioides sp. ZHH-013: 3-keto-Deoxynivalenol and 3-epi-Deoxynivalenol as Intermediate Products - Zhang, Honghai; Zhang, Heng; Qin, Xing; Wang, Xiaolu; Wang, Yuan; Bin, Yao; Xie, Xiangming; Zheng, Fei; Luo, Huiying (Frontiers in Microbiology, 2021)
Deoxynivalenol (DON) is one of the most devastating and notorious contaminants in food and animal feed worldwide. A novel DON-degrading strain, Nocardioides sp. ZHH-013, which exhibited complete mineralization of DON, was isolated from soil samples. The intermediate products of DON generated by this strain were identified by high-performance liquid chromatography and ultra-performance liquid chromatography tandem mass spectrometry analyses. It was shown that, on an experimental level, 3-keto-DON was a necessary intermediate product during the conversion from DON to 3-epi-DON. Further, the ZHH-013 strain could also utilize 3-epi-DON. This DON degradation pathway is a safety concern for food and feed. The mechanism of DON and 3-epi-DON elimination will be further studied, so that new enzymes for DON degradation can be identified.